2014
DOI: 10.3109/09638288.2014.948135
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain patients' beliefs about effective/ineffective constituents of a counseling intervention: a follow-up interview study

Abstract: Maintaining everyday activities, including retaining one's occupation, is an important factor in low back pain rehabilitation. Counselling on low back pain rehabilitation must be aligned with people's beliefs about their illness. A counselling intervention made patients adopt exercising into their long-term management of low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Two mixed-methods studies were excluded because it was not possible to differentiate data obtained with qualitative and quantitative methods [ 41 , 42 ]; a third study was excluded because we could not clearly identify the views reported by PwCDs [ 43 ]. This led to a total of 24 publications included in our review [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. The flow chart of the study selection process is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two mixed-methods studies were excluded because it was not possible to differentiate data obtained with qualitative and quantitative methods [ 41 , 42 ]; a third study was excluded because we could not clearly identify the views reported by PwCDs [ 43 ]. This led to a total of 24 publications included in our review [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. The flow chart of the study selection process is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Participants in the included qualitative studies were most often persons suffering from mental disorders [ 44 , 45 , 46 , 48 , 50 , 52 , 56 , 59 , 60 , 61 , 62 , 63 , 67 ]. Three studies included persons with musculoskeletal disorders [ 47 , 51 , 55 ], two studies persons with cancer [ 49 , 66 ], two studies persons with mental and musculoskeletal disorders [ 53 , 64 ], and two studies a broad mix of persons with long-term conditions [ 54 , 65 ]. In the remaining two studies, participants had disabilities related to different health conditions [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations